Mengendalikan Aksi Vandalisme Terhadap Situs Benteng Pendem Dengan Menggunakan Kuburan Palsu - Darwanto, Agus; Nurmarwaa, Syarifa; Surachman, Vitriyah Arafah (Prabayaksa: Journal of History Education, 2023)
Vandalism in the form of wall scribbles with the intention of leaving a mark at a tourist spot is a bad habit that visitors often engage in. The aim of this research is to investigate the effectiveness of fake graves in stopping acts of vandalism by visitors at Benteng Pendem. The research method used is a mix of qualitative and quantitative methods. Qualitative data was collected through snowball sampling, and quantitative data was collected through a survey using a questionnaire. The most common act of vandalism by visitors at Benteng Pendem is wall scribbles and graffiti. The frequency of such vandalism has decreased since the installation of revered fake graves. There is a correlation between respondents' belief in the sanctity of the fake graves and their reduced willingness to engage in acts of vandalism, with a reduction rate of 37.4% and an impact rate of 12% in controlling acts of wall scribbles at Benteng Pendem.